APLIKASI INSEKTISIDA NABATI BERBAHAN TUMBUHAN RAWA PADA HAMA PENGGEREK POLONG KEDELAI DI LAHAN RAWAPASANG SURUT - Ni'matuljannah Akhsan (Agrifarm : Jurnal Ilmu Pertanian, 2020)
ABSTRACT The aim of this research is to control environmentally friendly soybean pod borer by utilizing plants in swamps as a vegetable insecticide, namely Kepayang (Pangiumedule). The study was conducted on tidal land in the Village of Kiri Dalam, Barambai District, Barito Kuala Regency, South Kalimantan Province. The study was designed in a randomized block design with 5 replications. The treatment is; 1. Kepayang leaf extract, 2. Without control, 3.Neem plant extract, 4. Chloriliprol insecticide. The results showed that the Kepayang leaf extract can be used as a botanical insecticide controlling soybean pod borer because it can suppress soybean pod attack by up to 62% and is no different from the Chloriliprol insecticide treatment by 64%. Keywords: Applications, Swamp Plants, Boring Pods Borers, Tidal Swamps